Visible Light Communication and Augmented Reality for Underground Positioning System - Riurean Simona; Olar Marius; Ionică Andreea; Pellegrini Lilla (MATEC Web of Conferences, 2020)
Visible Light Communication (VLC) technology allows wireless data transmission piggybacked by illumination. Highly accurate and reliable systems based on VLC, as Indoor Positioning System (IPS) have been already developed by academics and specialized companies. Underground Positioning System (UPS) addressed here is embedded into the protection equipment, compulsory to be used underground, being therefore important to workers in potential dangerous spaces since fast data communication and real-time data interpretation is therefore possible. This paper presents the VLC technology implemented in mining underground specific environment for an accurate positioning and fast data communication for underground navigation with the main aim of developing a real time warning and alarming system based on Augmented Reality (AR) and Neural Networks (NNs) principles.